2021
DOI: 10.1029/2020ja028616
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Upstream Proton Cyclotron Wave Properties and Occurrence at Mars Observed by MAVEN

Abstract: The presence of plasma waves upstream from the Martian bow shock, with frequencies near the local proton cyclotron frequency in the spacecraft frame, constitutes, in principle, an indirect signature for the existence of planetary protons from the ionization of Martian exospheric hydrogen. In this study, we determine the "proton cyclotron wave” (PCW) occurrence rate between October 2014 and February 2020, based on Magnetometer and Solar Wind Ion Analyzer measurements from the Mars Atmosphere and Volatile Evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 74 publications
7
40
0
Order By: Relevance
“…By analyzing MAVEN MAG observations between October 2014and March 2016, Romanelli et al (2016 reported that the PCW occurrence rate upstream of the Martian bow shock varies with time and takes higher values near the Martian perihelion. Romeo et al (2021) confirmed such annual periodicity of PCWs occurrence rate upstream from the Martian bow shock for three Martian perihelia, analyzing MAVEN MAG and Solar Wind Ion Analyzer (SWIA) data between October 2014 and February 2020. This long-term trend has been associated with the seasonal variability of the Martian H exosphere, that extends well beyond the Martian bow shock, and provides the source of newborn planetary protons (e.g., Bhattacharyya et al 2015;Chaffin et al 2014;Clarke et al 2017;Yamauchi et al 2015;Rahmati et al 2017;Halekas 2017;Halekas et al 2020;Halekas & McFadden 2021).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…By analyzing MAVEN MAG observations between October 2014and March 2016, Romanelli et al (2016 reported that the PCW occurrence rate upstream of the Martian bow shock varies with time and takes higher values near the Martian perihelion. Romeo et al (2021) confirmed such annual periodicity of PCWs occurrence rate upstream from the Martian bow shock for three Martian perihelia, analyzing MAVEN MAG and Solar Wind Ion Analyzer (SWIA) data between October 2014 and February 2020. This long-term trend has been associated with the seasonal variability of the Martian H exosphere, that extends well beyond the Martian bow shock, and provides the source of newborn planetary protons (e.g., Bhattacharyya et al 2015;Chaffin et al 2014;Clarke et al 2017;Yamauchi et al 2015;Rahmati et al 2017;Halekas 2017;Halekas et al 2020;Halekas & McFadden 2021).…”
Section: Introductionsupporting
confidence: 58%
“…It is worth emphasizing that, although this term (proton cyclotron waves) has been used very often to make reference to them, they are not associated with the ion cyclotron wave mode. Temporal variability in the PCWs occurrence rate has been reported based on Mars Global Surveyor magnetic field observations (Bertucci et al 2013;Romanelli et al 2013) and more recently with MAVEN Magnetometer (MAG) measurements (Connerney et al 2015;Jakosky et al 2015;Romanelli et al 2016;Romeo et al 2021). By analyzing MAVEN MAG observations between October 2014and March 2016, Romanelli et al (2016 reported that the PCW occurrence rate upstream of the Martian bow shock varies with time and takes higher values near the Martian perihelion.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These cyclotron waves have well‐defined frequencies at fci=qB2πmi ${f}_{ci}=\frac{qB}{2\pi {m}_{i}}$, where q is the charge of an electron, B is the magnetic field, and m i is the mass of the ion species i . We note that in this study, the term ICW, when at the proton gyrofrequency, is not the same as proton cyclotron waves, which are related to newborn pickup protons (e.g., Halekas et al., 2020; Romanelli et al., 2016; Romeo et al., 2020; Ruhunusiri et al., 2016). B is observable using the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission magnetometer (MAG) (Connerney et al., 2015; Jakosky, Grebowsky, et al., 2015; Jakosky, Lin, et al., 2015).…”
Section: Introductionmentioning
confidence: 70%
“…same as proton cyclotron waves, which are related to newborn pickup protons (e.g., Halekas et al, 2020;Romanelli et al, 2016;Romeo et al, 2020;Ruhunusiri et al, 2016). B is observable using the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission magnetometer (MAG) (Connerney et al, 2015;Jakosky, Lin, et al, 2015).…”
mentioning
confidence: 99%